Structural stability analysis of proposed Budhi Gandaki dam and optimization - Bimal Ojha; Hari Ram Parajuli (Journal of Innovations in Engineering Education, 2023)
High-rise arch dams are frequently employed in the construction of large storage-type hydropower projects due to their cost-effectiveness. This study presents the comparison in stress and deformation behavior of concrete dam and concrete face rock-fill dam under worst combination of loads. For illustrative purpose, the proposed double curvature arch dam of Budhigandaki Hydroelectric Project is chosen with some modifications. This study proposed the 3-D finite element method (FEM) for stress and deformation analysis of dam considering material non-linearity between concrete and rock-fill material following Drucker-Prager yield criteria. The proposed methodology is implemented through ANSYS 2021. The hydrodynamic pressure of reservoir water is modeled as added mass using Westergaard approach. The compressive and tensile stress developed in both types of dams are investigated and analyzed for different load combinations. The force acting at base of dam and deformation at crest level is also investigated. The results for both types of dam are found to be comparable which suggests that the wasteful volume of concrete can be replaced by consolidated soil (rock-fill) to decrease the overall construction cost of project.